Inorganic composite polyurethane material containing dynamic borate bonds and preparation method thereof
By introducing dynamic borate bonds and nanomaterials into polyurethane materials, the problem of low mechanical and thermodynamic properties of polyurethane materials is solved, and the self-healing and recyclability of the material is achieved.
Patent Information
- Application Number
- CN202411821362.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
Existing polyurethane materials have problems with low mechanical properties and low thermodynamic properties, and are difficult to recycle and degrade, resulting in waste of resources and environmental pollution.
By introducing dynamic borate bonds and nanomaterials, boric acid compounds react with triethanolamine to prepare boron ester-based diol monomers, and react with polyurethane prepolymer and modified nanomaterials to form an inorganic composite polyurethane material containing dynamic borate bonds.
It significantly improves the mechanical and thermodynamic properties of the material, while at the same time, the degradation and recovery of the material under mild conditions, extending the service life of the material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material industry, and in particular to an inorganic composite polyurethane material containing dynamic borate ester bonds and a preparation method thereof. Background Art
[0002] In recent years, polyurethane (PU) materials have attracted attention from all walks of life due to their excellent performance and wide application in many fields. However, their difficulty in recycling and degradation has caused large-scale resource waste and environmental pollution. By introducing dynamic covalent bonds into the material, the bond exchange reaction is activated by heat, light, pH and catalysts to rearrange the structure, which can greatly extend the service life of the polyurethane (PU) material. Common dynamic covalent bonds include DA bonds, borate bonds, disulfide bonds, imine bonds, acyl hydrazone bonds, hydrogen bonds, host-guest interactions, metal coordination bonds, etc. The material with dynamic covalent bonds introduced in this way has the strength and chemical stability of traditional thermosetting plastics, and at the same time can show the reproducibility of thermoplastics. We also call this material a self-healing material; Among them, the borate bond is a special dynamic covalent bond that can form a bond in a short time. It will decompose when it encounters water, and can regenerate the borate bond after removing the water (the bond energy of the BO bond is as high as 809 kJ / mol). This reversible hydrolysis reaction gives the material self-healing ability and has significant self-healing ability. It is often used to prepare high-strength self-healing polyurethane materials. However, in current research, self-healing polyurethanes based on borate bonds have the problems of low mechanical properties and low thermodynamic properties. Studies have found that borate compounds containing borate bonds with nitrogen-boron internal coordination can significantly improve mechanical and thermodynamic properties. This coordination also plays the role of a sacrificial bond, which can effectively dissipate significant energy during stretching.
[0003] Incorporation of nanofillers is a widely used method to improve the mechanical properties of polymer materials. Nanomaterials such as nano-calcium carbonate, carbon nanotubes, graphene, silica nanoparticles and nanofibers have been introduced to enhance the mechanical properties of many polymer systems; In summary, how to introduce nanomaterials and borate bonds into polyurethane materials, and how to improve the thermal stability and mechanical properties of the materials have become urgent issues to be addressed. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an inorganic composite polyurethane material containing dynamic borate bonds and a preparation method, which uses cheap and readily available inorganic nanocomposite materials to effectively enhance the thermal mechanical properties of the material. At the same time, the synergistic effect of borate bonds and boron-nitrogen coordination enables the material to be degraded and recycled under mild conditions, providing a new idea for the preparation of polyurethane self-healing materials.
[0005] The present invention is achieved through the following technical solutions: A method for preparing an inorganic composite polyurethane material containing dynamic borate ester bonds, comprising: S1, dissolving a boric acid compound in anhydrous ethanol, dropping triethanolamine, heating in a water bath under a nitrogen atmosphere for reaction, and post-treating the obtained product to obtain a boron ester diol monomer; S2, reacting the alcohol aqueous solution of the nanomaterial with the alcohol aqueous solution of the silane coupling agent under a nitrogen atmosphere, and performing post-treatment on the obtained product to obtain a modified nanomaterial.
[0006] S3, dissolving a set ratio of a polyglycol compound and a diisocyanate compound in a solvent C, adding a catalyst, and reacting in a nitrogen atmosphere to obtain a polyurethane prepolymer; S4, after dissolving the boronic acid ester diol monomer and the diamine compound in solvent C, adding a crosslinking agent, stirring and heating the reaction, adding the resultant to the polyurethane prepolymer, and then adding the modified nanomaterial dissolved in solvent C. After the reaction is completed, the solvent C is removed to prepare an inorganic composite polyurethane material containing dynamic boric acid ester bonds.
[0007] Preferably, the molar ratio of the boric acid compound to triethanolamine in S1 is 2:1, and the sum of the masses of the boric acid compound and triethanolamine in S1 accounts for 40 wt%-60 wt% of the anhydrous ethanol.
[0008] Preferably, the mass ratio of the silane coupling agent to the nanomaterial in S1 is 1:10; The addition ratio of the nanomaterial, anhydrous ethanol and distilled water in the alcohol aqueous solution of the nanomaterial is 5g: 180ml: 20ml; The volume ratio of the silane coupling agent, anhydrous ethanol and distilled water in the alcohol aqueous solution of the silane coupling agent is 1:12:1.
[0009] Preferably, the boric acid compound is 1,4-phenylenediboric acid; the silane coupling agent is KH-550; the polyglycol compound is polypropylene glycol; the diisocyanate compound is isophorone diisocyanate; the catalyst is dibutyltin dilaurate; and the diamine compound is 4,4-diaminodiphenylmethane.
[0010] Preferably, the cross-linking agent comprises one of triethanolamine and propyl gallate.
[0011] Preferably, the nano material includes one of nano silicon dioxide, nano calcium carbonate and nano titanium dioxide.
[0012] Preferably, the molar ratio of the polyglycol compound to the diisocyanate compound in S3 is 1:2-1:4, the molar ratio of the boryl diol monomer to the diamine compound is 1:5, and the molar ratio of the boryl diol monomer to the crosslinking agent is 1:2.
[0013] Preferably, solvent C is N,N-dimethylacetamide.
[0014] Preferably, the reaction temperature in S1 is 65-70°C, and the reaction time is 2h-3h, the reaction temperature in S2 is 60-75°C, and the reaction time is 4h-6h; the reaction temperature in S3 is 80-120°C, and the reaction time is 6h-10h.
[0015] An inorganic composite polyurethane material containing dynamic borate ester bonds is prepared by the preparation method of the inorganic composite polyurethane material containing dynamic borate ester bonds.
[0016] An inorganic composite polyurethane material containing dynamic borate ester bonds is prepared by the above preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The invention provides a method for preparing an inorganic composite polyurethane material containing a dynamic borate ester bond. First, a borate ester diol monomer is prepared using a boric acid compound and triethanolamine as raw materials. The diol compound is reacted with a polyurethane prepolymer to obtain a polyurethane compound containing a borate ester bond. On this basis, a diamine compound is introduced for chain extension. The obtained self-repairing polyurethane material is used as a matrix, low-cost nano calcium carbonate and nano silicon dioxide are used as inorganic composite materials, silicon dioxide and calcium carbonate are selected as functional fillers, and nano materials are doped therein. A recyclable and ductile polyurethane glass polymer material is prepared by a gradient temperature curing method. Based on the principle that a nitrogen donor compound can "lock" the empty orbit of a boron atom to stabilize the borate ester bond, boron-nitrogen internal coordination is introduced into the borate ester diol monomer, and the synergy between the borate ester bond and the boron-nitrogen internal coordination can significantly improve the mechanical properties and thermodynamic properties of the material. The longer flexible chain segments in the polyurethane prepolymer can give the material soft and stretch-resistant properties, and the benzene ring structure in the diamine chain extender can increase the rigidity and thermal stability of the material.
[0018] Furthermore, the present invention prepares a boron ester-containing diol monomer, thereby introducing a dynamic covalent bond, performing surface modification on the nanocomposite material, and doping it into polyurethane by a blending method, so that the obtained polyurethane self-healing material can be degraded under certain stimulation. The nanocomposite material has a large breakdown field strength, high flexibility, low heating temperature, light material, and low cost, which improves the mechanical properties and thermal stability of the material to a certain extent. At the same time, the thermal mechanical properties of the material can also be adjusted by the soft and hard segment ratio of the crosslinking agent, which can further optimize the performance of the polyurethane self-healing material.
[0019] Furthermore, the inorganic composite polyurethane material containing dynamic borate bonds of the present invention has excellent mechanical properties, self-repairing properties, shape memory and reproducibility. The material can be degraded and recycled under various stimuli. The experimental raw materials in the design of the present invention are cheap and easy to obtain. The polyurethane polymer material has excellent mechanical properties, thermal stability and creep resistance, and has great application prospects in wearable electronic products, coatings, high-performance adhesives, sensors in biomedicine and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The reaction flow chart of Example 1, Example 3 and Example 5 is shown; Figure 2 The following is a reaction flow chart of Example 2, Example 4 and Example 6. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0022] The invention adopts boric acid compounds and triethanolamine to prepare a diol monomer containing a boron ester group, adds a diamine compound as a chain extender and different crosslinking agents into a polyurethane prepolymer, and then dopes the modified nano material into the prepolymer to obtain an inorganic composite polyurethane material containing a dynamic boric ester bond.
[0023] The technical scheme adopted by the present invention is as follows: the first step is to add a boric acid compound and triethanolamine in a molar ratio of 1:2 to a three-necked flask equipped with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condensation device, and then add a solvent, react in a water bath, and after reacting for 2-4 hours, the obtained product is filtered, and then recrystallized three times with ethanol, and dried to obtain a product containing a boron ester diol monomer. The second step is to first prepare a hydrolysis solution according to a volume ratio of silane coupling agent / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50°C for 1 hour. Then, the nano material particles and the alcohol-water mixed solution (the volume ratio of anhydrous ethanol to water is 9 / 1) are added to a beaker and ultrasonically dispersed for 1 hour. After that, the alcohol-water mixed solution of the nano material particles and the silane coupling agent hydrolysis solution (the coupling agent addition amount is about 10% of the mass fraction of the nano material) are added to a round-bottom flask together, heated at 70°C and condensed and refluxed, and the reaction time is 6 hours. After the reaction, the product was centrifuged and ultrasonically cleaned with anhydrous ethanol for more than 3 times, and finally the product was vacuum dried at 60 °C for 24h. Step 3: Take polydiol and diisocyanate in a molar ratio of 1:2-1:6, dissolve them in a solvent and place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser, add 0.05-0.15 g of catalyst, and react at 80 °C for 4h to obtain a -NCO-terminated polyurethane prepolymer; add boron ester diol monomer, crosslinker, and diamine to the prepolymer in a molar ratio of 1:2:5, react at 80 °C for 6h, and finally remove different mass fractions of nanocomposites dissolved in DMAC, doped into polyurethane, and reacted for 3h. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven and dried at 80 °C for 48h to volatilize most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0024] The boronic acid compound used in the first step is 1,4-phenylenediboronic acid.
[0025] The solvent is anhydrous ethanol and N,N-dimethylacetamide (DMAC).
[0026] The detergent is anhydrous ethanol and water.
[0027] The composite material described in the second step is nano silicon dioxide, nano titanium dioxide and nano calcium carbonate.
[0028] The coupling agent is KH-550.
[0029] The polyglycol described in the third step is polypropylene glycol (PPG).
[0030] The diisocyanate is isophorone diisocyanate (IPDI).
[0031] The diamine compound is 4,4'-diaminodiphenylmethane.
[0032] The catalyst is dibutyltin dilaurate (DBTDL).
[0033] The cross-linking agent is triethanolamine and propyl gallate (PG).
[0034] Reaction equation: Reaction equation of diols containing borate ester bonds:
[0035] Embodiment 1: Step 1: Dissolve 1,4-phenylenediboronic acid (3.32 g, 10 mmol) in anhydrous ethanol, and then add triethanolamine (5.98 g, 20 mmol) into a three-necked flask. After condensation and reflux at 40 °C for 2h, the solution turns white and turbid. After the reaction is completed, the reaction product is filtered to obtain white crystals, which are then washed three times with ethanol and dried in an oven at 70 °C for 24h. Finally, a diol with a boric acid ester bond is obtained in the form of a white powder, named TB-OH.
[0036] Step 2: First, take 1 mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50 ℃ for 1h. Then add 5 g of nano-CaCO3 particles and 180 ml of anhydrous ethanol and 20 ml of water mixed solution (the volume ratio of anhydrous ethanol to water is 9:1) into a beaker and ultrasonically disperse for 1h. Then add the alcohol-water mixed solution of CaCO3 and the KH-550 hydrolysis solution (the amount of coupling agent added is about 10% of the mass fraction of CaCO3) into a round-bottom flask, heat and condense under reflux at 80 ℃, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60 ℃ for 24h.
[0037] Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI), dissolve them in 10 g of N, N-dimethylacetamide (DMAC), place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet, add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 ° C for 4 h to obtain a -NCO-terminated polyurethane prepolymer; the boron ester diol monomer TB-OH (0.78 g, 2 mmol), cross-linking agent triethanolamine (0.60 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), 6 mL of DMF solvent were heated for 1 h and then added to the prepolymer, and reacted at 80 ° C for 6 h. Finally, the modified nano-calcium carbonate (0.1821 g, 1%wt of polyurethane material) was dissolved in 5ml DMAC, ultrasonicated for 2h, and doped into polyurethane for 3h. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80°C for 24h to evaporate most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0038] Embodiment 2: Step 1: Dissolve 1,4-phenylenediboronic acid (3.32 g, 10 mmol) in anhydrous ethanol, and then add triethanolamine (5.98 g, 20 mmol) into a three-necked flask. After reflux at 40 °C for 2 hours, the solution turns white and turbid. After the reaction is completed, the reaction product is filtered to obtain white crystals, which are then washed three times with ethanol and dried in an oven at 70 °C for 24 hours to obtain a white powder named TB-OH.
[0039] Step 2: First, take 1 mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50°C for 1h. Then add 5 g of nano-SiO2 particles and a mixed solution of 180 ml of anhydrous ethanol and 20 ml of water (the volume ratio of anhydrous ethanol to water is 9 / 1) into a beaker and ultrasonically disperse for 1h. Then add the alcohol-water mixed solution of SiO2 and the KH-550 hydrolysis solution (the amount of coupling agent added is about 10% of the mass fraction of SiO2) into a round-bottom flask, heat and condense under reflux at 70°C, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60°C for 24h.
[0040] Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI) and dissolve them in 10 g of N, N-dimethylacetamide (DMAC) and place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet, add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 ° C for 4 h to obtain a -NCO-terminated polyurethane prepolymer; boron ester diol monomer TB-OH (0.78 g, 2 mmol), cross-linking agent propyl gallate (PG) (0.85 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), 6 mL of DMF solvent were heated for 1 h and then added to the prepolymer, and reacted at 80 ° C for 6 h. Finally, the modified nano-CaCO3 (0.1821 g, 1wt% of polyurethane material) was dissolved in 5ml DMAC, ultrasonicated for 2h, and doped into polyurethane for 3h. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80°C for 24 hours to evaporate most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0041] Embodiment three: Step 1: If Figure 1 As shown, 1,4-phenylenediboronic acid (3.32 g, 10 mmol) was dissolved in anhydrous ethanol, and triethanolamine (5.98 g, 20 mmol) was added to a three-necked flask. After condensation and reflux at 40 °C for 2h, the solution turned white and turbid. After the reaction was completed, the reaction product was filtered to obtain white crystals, which were then washed three times with ethanol and dried in an oven at 70 °C for 24h to obtain a white powder named TB-OH. Step 2: First, take 1 mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50 ℃ for 1h. Then add 5 g of nano-SiO2 particles and 180 ml of anhydrous ethanol and 20 ml of water mixed solution (the volume ratio of anhydrous ethanol to water is 9:1) into a beaker and ultrasonically disperse for 1h. Then add the alcohol-water mixed solution of SiO2 and the KH-550 hydrolysis solution (the amount of coupling agent added is about 10% of the mass fraction of SiO2) into a round-bottom flask, heat and condense under reflux at 70 ℃, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60 ℃ for 24h. Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI), dissolve them in 10 g of N, N-dimethylacetamide (DMAC), place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet, add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 ° C for 4 h to obtain a -NCO-terminated polyurethane prepolymer; boron ester diol monomer TB-OH (0.78 g, 2 mmol), cross-linking agent triethanolamine (0.60 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), 6 mL of DMF solvent are heated for 1 h and then added to the prepolymer, and reacted at 80 ° C for 6 h. Finally, the modified nano-SiO2 (0.1821 g, 1 wt % of the polyurethane material) was dissolved in 5 ml of DMAC, ultrasonicated for 2 h, and doped into the polyurethane for 3 h. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80 ° C for 24 h to evaporate most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0042] Embodiment 4: Step 1: Dissolve 1,4-phenylenediboronic acid (3.32 g, 10 mmol) in anhydrous ethanol, and then add triethanolamine (5.98 g, 20 mmol) into a three-necked flask. After reflux at 40 °C for 2 hours, the solution turns white and turbid. After the reaction is completed, the reaction product is filtered to obtain white crystals, which are then washed three times with ethanol and dried in an oven at 70 °C for 24 hours to obtain a white powder named TB-OH. Step 2: First, take 1mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50 ℃ for 1h. Then add 5g of nano-SiO2 particles and 180ml of anhydrous ethanol and 20ml of water mixed solution (the volume ratio of anhydrous ethanol to water is 9 / 1) into a beaker and ultrasonically disperse for 1h. Then add the alcohol-water mixed solution of SiO2 and the KH-550 hydrolysis solution (the amount of coupling agent added is about 10% of the mass fraction of SiO2) into a round-bottom flask, heat and condense under reflux at 70 ℃, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60℃ for 24h.
[0043] Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI), dissolve them in 10 g of N, N-dimethylacetamide (DMAC), place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet, add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 °C for 4 hours to obtain a -NCO-terminated polyurethane prepolymer; the boron ester diol monomer TB-OH (0.78 g, 2 mmol), the cross-linking agent propyl gallate (PG) (0.85 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), 6 mL of DMF solvent were heated for 1 hour and then added to the prepolymer, and reacted at 80 °C for 6 hours. Finally, the modified nano-TiO2 (0.1821 g, 1wt% of polyurethane material) was dissolved in 5ml DMAC, ultrasonicated for 2h, and doped into polyurethane for 3h. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80°C for 24h to evaporate most of the solvent and volatiles, and the final glass-like elastomer was obtained.
[0044] Embodiment five: Step 1: Dissolve 1,4-phenylenediboronic acid (3.32 g, 10 mmol) in anhydrous ethanol, and then add triethanolamine (5.98 g, 20 mmol) into a three-necked flask. After condensation and reflux at 40 °C for 2 hours, the solution turns white and turbid. After the reaction is completed, the reaction product is filtered to obtain white crystals, which are then washed three times with ethanol and dried in an oven at 70 °C for 24 hours to obtain a white powder named TB-OH. Step 2: First, take 1mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50 ℃ for 1h. Then add 5g of nano-TiO2 particles and 180ml of anhydrous ethanol and 20ml of water mixed solution (the volume ratio of anhydrous ethanol to water is 9:1) into a beaker and ultrasonically disperse for 1h. Then add the TiO2 alcohol-water mixed solution and KH-550 hydrolysis solution (the coupling agent addition amount is about 10% of the mass fraction of TiO2) into a round-bottom flask, heat and condense under reflux at 70 ℃, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60 ℃ for 24h.
[0045] Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI), dissolve them in 10 g of N, N-dimethylacetamide (DMAC), and place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet. Add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 °C for 4 hours to obtain a -NCO-terminated polyurethane prepolymer; heat the boron ester diol monomer TB-OH (0.78 g, 2 mmol), cross-linking agent propyl gallate (PG) (0.85 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), and 6 mL of DMF solvent for 1 hour, then add them to the prepolymer and react at 80 °C for 6 hours. Finally, the modified nano-TiO2 (0.1821 g, 1wt% of polyurethane material) was dissolved in 5 ml DMAC, ultrasonicated for 2 hours, and doped into polyurethane for 3 hours. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80 ° C for 24 hours to evaporate most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0046] Embodiment six: Step 1: Dissolve 1,4-phenylenediboronic acid (3.32 g, 10 mmol) in anhydrous ethanol, and then add triethanolamine (5.98 g, 20 mmol) into a three-necked flask. After condensation and reflux at 70 °C for 2 hours, the solution turns white and turbid. After the reaction is completed, the reaction product is filtered to obtain white crystals, which are then washed three times with ethanol and dried in an oven at 70 °C for 24 hours to obtain a white powder named TB-OH. Step 2: First, take 1 mL of KH-550 silane coupling agent, prepare the hydrolysis solution according to the volume ratio of KH-550 / deionized water / anhydrous ethanol = 1:1:12, and stir and hydrolyze at 50 ℃ for 1h. Then add 5 g of nano-TiO2 particles and a mixed solution of 180 ml of anhydrous ethanol and 20 ml of water (the volume ratio of anhydrous ethanol to water is 9:1) to a beaker and ultrasonically disperse for 1h. Then add the alcohol-water mixed solution of TiO2 and the KH-550 hydrolysis solution (the amount of coupling agent added is about 10% of the mass fraction of TiO2) to a round-bottom flask, heat and condense under reflux at 70 ℃, and the reaction time is 6h. After the reaction, centrifuge the product, and ultrasonically clean it with anhydrous ethanol for more than 3 times, and finally vacuum dry the product at 60 ℃ for 24h.
[0047] Step 3: Take 9 g (10 mmol) of polypropylene glycol 1000 (PPG) and 6.00 g (27 mmol) of isophorone diisocyanate (IPDI), dissolve them in 10 g of N, N-dimethylacetamide (DMAC), place them in a 250 mL three-necked flask with an electric stirrer, a pure nitrogen protection device inlet, and a reflux condenser inlet, add 0.1 g of dibutyltin dilaurate (DBTDL) catalyst, and react at 80 °C for 4 hours to obtain a -NCO-terminated polyurethane prepolymer; heat the boron ester diol monomer TB-OH (0.78 g, 2 mmol), cross-linking agent propyl gallate (PG) (0.85 g, 4 mmol), 4,4'-diaminodiphenylmethane (1.98 g, 10 mmol), and 6 mL of DMF solvent for 1 hour, then add them to the prepolymer and react at 80 °C for 6 hours. Finally, the modified nano-TiO2 (0.1821 g, 1wt% of polyurethane material) was dissolved in 5 ml DMAC, ultrasonicated for 2 hours, and doped into polyurethane for 3 hours. The obtained product was filtered and evenly spread on a polytetrafluoroethylene plate, placed in an oven at 80 ° C for 24 hours to evaporate most of the solvent and volatiles, and the final glass-like polymer material was obtained.
[0048] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an inorganic composite polyurethane material containing a dynamic borate ester bond, characterized in that: include: S1, dissolving a boric acid compound in anhydrous ethanol, dropping triethanolamine, heating in a water bath under a nitrogen atmosphere for reaction, and post-treating the obtained product to obtain a boron ester diol monomer; S2, reacting the alcohol aqueous solution of the nanomaterial with the alcohol aqueous solution of the silane coupling agent under a nitrogen atmosphere, and post-treating the obtained product to obtain a modified nanomaterial; S3, dissolving a set ratio of a polyglycol compound and a diisocyanate compound in a solvent C, adding a catalyst, and reacting in a nitrogen atmosphere to obtain a polyurethane prepolymer; S4, after dissolving the boronic acid ester diol monomer and the diamine compound in solvent C, adding a crosslinking agent, stirring and heating the reaction, adding the resultant to the polyurethane prepolymer, and then adding the modified nanomaterial dissolved in solvent C. After the reaction is completed, the solvent C is removed to prepare an inorganic composite polyurethane material containing dynamic boric acid ester bonds.
2. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The molar ratio of the boric acid compound to triethanolamine in S1 is 2:1, and the sum of the masses of the boric acid compound and triethanolamine in S1 accounts for 40 wt%-60 wt% of the anhydrous ethanol.
3. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The mass ratio of silane coupling agent to nanomaterial in S1 is 1:10; The addition ratio of the nanomaterial, anhydrous ethanol and distilled water in the alcohol aqueous solution of the nanomaterial is 5g: 180ml: 20ml; The volume ratio of the silane coupling agent, anhydrous ethanol and distilled water in the alcohol aqueous solution of the silane coupling agent is 1:12:
1.
4. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The boric acid compound is 1,4-phenylenediboric acid; the silane coupling agent is KH-550; the polyglycol compound is polypropylene glycol; the diisocyanate compound is isophorone diisocyanate; the catalyst is dibutyltin dilaurate; and the diamine compound is 4,4-diaminodiphenylmethane.
5. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The cross-linking agent includes one of triethanolamine and propyl gallate.
6. The inorganic composite polyurethane material containing dynamic borate bonds and the preparation method according to claim 1, characterized in that: The nano material includes one of nano silicon dioxide, nano calcium carbonate and nano titanium dioxide.
7. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The molar ratio of the polyglycol compound to the diisocyanate compound in S3 is 1:2-1:4, the molar ratio of the boryl diol monomer to the diamine compound is 1:5, and the molar ratio of the boryl diol monomer to the crosslinking agent is 1:
2.
8. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: Solvent C is N,N-dimethylacetamide.
9. The method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to claim 1, characterized in that: The reaction temperature in S1 is 65-70°C, and the reaction time is 2h-3h; the reaction temperature in S2 is 60-75°C, and the reaction time is 4h-6h; the reaction temperature in S3 is 80-120°C, and the reaction time is 6h-10h.
10. An inorganic composite polyurethane material containing dynamic borate bonds, prepared according to the method for preparing an inorganic composite polyurethane material containing dynamic borate bonds according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of weather-resistant polyurethane resin and application of weather-resistant polyurethane resin in powder coating
CN118515842A
Waterproof acid and alkali-resistant polyurethane elastomer material with synergistic effect of hydrogen bonds and coordinate bonds and preparation method of waterproof acid and alkali-resistant polyurethane elastomer material
CN118580461A
Preparation method of self-repairing polyurethane material and application of self-repairing polyurethane material in tire tube
CN118725545A
Polyurethane glass body capable of being remolded and hydrolyzed, degraded and recycled as well as preparation method and application of polyurethane glass body
CN119060294A
Nanoparticle containing polyurethane dispersions affording materials having improved tensile strength and elongation
WO2014059597A1
Cited By
Polyurethane elastomer membrane material suitable for low-altitude aircraft rotor blade and preparation method of polyurethane elastomer membrane material
CN120842831A